2020
DOI: 10.1097/aco.0000000000000886
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperating room anesthesia in different parts of the world

Abstract: Purpose of review Advances in early diagnosis and treatment of diseases using minimally invasive procedures has led to an increase in the number of cases in locations outside the operating room. This surge created the need for anesthesia services to expand to these areas to provide well tolerated and favorable procedural conditions. The present review describes nonoperating room anesthesia patterns in different parts of the world. Recent findings Nonope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
4
0
4
Order By: Relevance
“…Patients presenting for gastroscopy are increasingly older and more frail 2 . Recently, remimazolam has been thought to be a new promising sedative for procedural sedation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients presenting for gastroscopy are increasingly older and more frail 2 . Recently, remimazolam has been thought to be a new promising sedative for procedural sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients presenting for gastroscopy are increasingly older and more frail. 2 Recently, remimazolam has been thought to be a new promising sedative for procedural sedation. In this trial, we found that combined with 0.2 μg/kg remifentanil, the ED95 induction dose to inhibiting movements of older patients undergoing gastroscopy was 0.2039 (95%CI 0.1753-0.3896) mg/kg for remimazolam besylate and 1.9944 (95%CI 1.7386-5.9553) mg/kg for propofol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El 80,4% fue ASA II y ASA III con una edad promedio de 56 años, y con una población mayor a 70 años del 26,8%. Hallazgos que pudieran ser similares a los reportados [6], [8], [9], [10]. En la revisión de Kim et al, se encontró que la edad mayor a 70 años era el 20% en AFQ frente al 12% en salas de cirugía y el 69% de los casos de AFQ estaban en las categorías III-V de ASA frente a 44% para casos de quirófano [8].…”
Section: Discussionunclassified
“…77,78 Allocation of Safety Research and Resources to Nonoperating Room Anesthesia Practices In many high-income countries, there is significant growth in numbers of surgical, interventional, and diagnostic procedures for which patients require anesthesia care performed in nonoperating room environments. 79,80 The provision of anesthesia services in these unique and often variable settings raises potential safety barriers related to interprofessional communications, infrastructure, and safety cultures. 81,82 As noted in a number of the summaries in this article, national anesthesiology societies are very interested in learning how to best address these potential barriers, ensure that standards of care are followed, and develop outcome reporting databases to track patient safety and, when appropriate, develop and implement patient care processes to improve safety.…”
Section: Elimination Of Punitive Outcomes and Criminalization Of Medi...mentioning
confidence: 99%